Use of Critical path method inmaintenance planning of an electric power station - Laith Noman Dawood; sawsan S.AL-zubaidy; Mahmoud Abbas Mahmoud (Engineering and Technology Journal, 2012)
In this work studying of the strategy of preventive maintenance in the station was conducted and spatial planning combustion chambers inspection (CI) by using the critical path method which an important tools for the planning of maintenance work was developed. In order to have accurate results for calculating early, latest, delay, and slack times, and determining the critical path time (WINQSB) Software which contain (CPM-BERT) programs has been used. .The most important results of this study is in reducing the time of preventive maintenance for combustion chambers inspection by two days. Furthermore, two other days can be saved if the time for some of critical activities was crashed.